A CLINICAL COMPARISION OF UROFLOW- DYNAMICS IN PATIENTS WITH LOWER URINARY TRACT SYMPTOMS AND THEIR PROSTATE SIZE USING SONOGRAPHY. - DR DEEPAK S; DR SANKARAN P K; DR GUNAPRIYA R; DR VIJAYALAKSHMI; DR VIJAYAKUMAR; MR YUVARAJ M (International Journal of Pharma and Bio Sciences, 2017)
Benign Prostatic hyperplasia (BPH) is a common entity among men over 40 years of age with significant disability. It is a condition that occurs when the enlarged prostate gland compresses the urethra leading to Bladder Outlet Obstruction (BOO). To compare the size of the prostate gland in patients with lower urinary tract symptoms with the extent of bladder outlet obstruction by uroflometry. 240 randomly selected male patients, between the age group of 41 to 70 years, with lower urinary tract symptoms, and underwent trans-abdominal sonogram and urine flowmetry. Based on the age group, the subjects were divided into 3 groups. In group 1 (41 to 50 years) there are totally 56 patients with LUTS, (over all 23%). Out of which 14 patients had BPH, indicating that about 5% of patients with LUTS have BPH. In Group 2 (51-60 years) there are totally 62 patients with LUTS, Out of which 20 patients had BPH, indicating that 9% of patients with LUTS have BPH. In Group 3 (61-70 years) there are totally 122 patients with LUTS, out of which 66 patients had BPH, indicating that 27% of patients with LUTS had BPH. The mean age of patients with lower urinary tract symptoms was 60 years with mean prostate size of 45 gms. 0 Enlarged prostate gland was observed in 41% of the patients with mean Q max of 14 ml/sec and post-voidal volume of 48ml. There was significant correlation between the age and the size of prostate gland. In elderly patients with lower urinary tract symptoms, can be due to benign prostatic hypertrophy. LUTS in early ages can be nonspecific to BPH and there was no significant correlation. Based on previous studies, atients between the ages of 41 to 60 years, with lower urinary tract symptoms, secondary to benign prostatic hypertrophy, are more likely to have increased post-voidal residual urine volume, following urine flowmetry.